An Antileukemic Glutaminase Free L-Asparaginase from Bacillus brevis - Azmi, Wamik; Narta, Umesh K.; Singh, Nishant; Gupta, Vibhor; Singh Kanwar, Shamsher; Devi, Sarita (Current Biotechnology, 2017)
Background: The antitumor activity of L-asparaginase isolated from natural sourceshas been proven thriving in treatment of acute lymphoblastic leukemia and other lymphoproliferative disorders however production efficiency and associated glutaminase activity has always been a limitation to its use. Asparaginase also induces apoptosis and cytoprotective autophagy in chronic myeloid leukemia cells. Together these findings make L-asparaginase a useful drug for the treatment of Acute Lymphocytic Leukemia and various other tumors. Methods: In the present study, the purification and characterization of a glutaminasefree intra-cellular L-asparaginase was done from Bacillus brevis, originally isolated from a cold desert region of Himachal Pradesh, India. Results: The enzyme was purified to 90-fold by a SulphopropylSephadex columnchromatography and found to be 32 kDa in molecular weight under reduced conditions. The enzyme possessed significant amount of activity at human physiological conditions of temperature (37°C) and pH (7.4) and have a half-life of 70 minutes at 25ºC. The Km and Vmax values of L-asparaginase were found to be 3.5 X 10-2 M and 0.77 IU, respectively. The L-asparaginase purified from B. brevis showed comparable in vitro toxicity on Hep-2C cell lines (91% survival) in comparison to commercial L-asparaginase preparation (90% survival) obtained from E. coli. Conclusion: L-asparaginase with high purity and high affinity for L-asparagine will bemost suitable for the treatment of lymphoblastic leukemia. The glutaminase free L-asparaginase obtained from B. brevis thus provides an additional therapeutic agent and could be used against for the treatment of various malignant diseases.
Keywords: intracellular enzyme